Level of ochratoxin A in cereal-flours in the Prishtina region - SPAHIU, Jeton; HUYBRECTHS, Bart; HOXHA, Rexhep; MALOKU-GJERGJI, Tahire; SHANDRO-ZEQIRI, Malbora; MUHARREMI, Hidajete; HAZIRI, Imer; RAMA, Adem (Phytopathologia Mediterranea, 2018)
To assess food safety associated with the occurrence of ochratoxin A (OTA) residues in different kinds of flours, a survey was carried out during 2016–2017 in 5 municipalities of the Prishtina region (Prishtina, Gllogovc, Lipjan, Fushë Kosova, and Podujevë). In the present study, a total of 120 flour samples were collected, consisting of domestic and imported samples. The analytical method used in our study to measure the occurrence and concentration range of OTA in the samples was competitive enzyme-linked immunosorbent assay (ELISA) method. A method based on UHPLC-MS/MS was used to confirm the presence of ochratoxin A in samples in which the toxin was detected by ELISA. Out of all the samples examined, nine were contaminated with OTA. The frequency of OTA contamination in 2016 was 5 out of 75 samples (6.7%), and in 2017, 4 out of 45 samples examined (8.9%) were contaminated. OTA was detected in four wheat flour samples (9%), in four maize flour samples (14.8%) and in one rye flour sample (8.3%). The level of OTA ranged from 0.26 to 0.85 μg kg-1 in the four positive wheat samples, from 0.77 to 2.75 μg kg-1 in the four positive maize samples and the level was 0.77 μg kg-1 in the one positive rye sample. None of the contaminated samples exceeded the maximum levels (ML) of 3 μg kg-1, set by to the European Union Regulation and Kosovo Food Codex.